Effect of Pressure Temperature on Physical and Mechanical Properties of Composite Mixtures with Recycled Polypropylene Plastic and Gmelina Bark (Gmelina arborea Roxb.) - Salima Ahmad, Alia
This research was conducted to identify the best composition and quality of recycled poly propylene plastic composite (RPP) and Gmelina bark (Gmelina arborea Roxb.) which were given MAH (Maleic Anhydride) on physical and mechanical properties due to variation in press temperature with remaining time and pressure press. RPP was used as a matrix, and Gmelina bark powder was used as a filler with a particle size of 40-60 mesh, while MAH was used as a modifier with the 5% use the matrix weight. The composition variation of ratio between filler and matrix used was 40:60 which was compressed at 170 ? for 4 minutes at press pressure of 30 kg / cm2. Variation in press temperature used was 170 ?, 165 ?, and 160 ?. The test analysis used was Analysis of Variance (ANOVA) and Duncan's continued test. The method was based on JIS A 5908-2003 standard. Test results showed the lowest KA value was 6.39%, the highest density was 1.03g / cm3, the lowest volume loss was 2.64%, the lowest thickness development was 0.77%, the lowest water absorption was 0.77%, the highest tensile strength was 25.75, the highest MOR value (Modulus of Rupture) was 90.34 kg / cm2, and the MOE (Modulus of Elasticity) value was 4149.67 kg / cm2. When viewed from physical and mechanical tests, the best press temperature was 170 ?.